Communication Policy In Realizing A Great North Labuhan Batu Through The “Regency Of Ngantor” Program In The Village” With An Islamic Communication Perspective - Sampurna, Ahmad; Thamrin, Ahmad; Sazali, Hasan (Faculty of Law, Universitas Pekalongan, 2024)
Regent of Ngantor in Villages (BungDesa) is a national program launched by the Minister of Villages, Development of Disadvantaged Regions and Transmigration of the Republic of Indonesia. This program is widely known by the public, because with the help of various media, it has become a national agenda which is expected to provide great benefits for accelerating development, especially in rural areas. This research used a qualitative approach with the research location being carried out in North Labuhan Batu with the time allocated for this research being 13 months from February 2023 to February 2024. The research informants were 5 people and were supported by elements of the community. Data collection used a triangulation approach (observation, interviews and documentation). Data analysis uses three stages, namely data reduction, data presentation and drawing conclusions. So that the validity of the data and the credibility of the research results can be trusted and correct. The research results show that 1) The Ngantor Village Regent Program is an initiative aimed at bringing local government closer to rural communities and increasing access to public services at the village level. 2) The Ngantor District Government program in this village is also in line with the ideals of